2023
DOI: 10.3389/fendo.2023.1216718
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between hearing impairment and the Triglyceride Glucose Index: based on a national cross-sectional study

Long Liu,
Maolin Qin,
Jiabiao Ji
et al.

Abstract: ObjectiveData from the National Health and Nutrition Examination Survey (NHANES) were used to assess the association between the triglyceride-glucose (TyG) index and hearing impairment (HI).MethodsWe used eight survey cycles from NHANES 2001–2012 and 2015–2018 to conduct this cross-sectional study. HI was designed as an dependent variable, and the TyG index was selected as an exposure factor (independent variable). The correlation between the two variables was assessed using multiple logistic regression. In or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…To address this limitation, the TyG index has been developed, which is superior to HOMA-IR in evaluating IR [ 24 , 25 ]. Mounting evidence reveals that TyG-based indexes are associated with diseases related to chronic inflammation or metabolic disorders, including arterial stiffness [ 26 ], albuminuria [ 27 ], nonalcoholic fatty liver disease [ 28 , 29 ], hearing impairment [ 30 ], and testosterone deficiency [ 31 ]. A recent finding reported that the TyG index had a linkage to CVD in patients with ischemic heart failure after percutaneous coronary intervention [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…To address this limitation, the TyG index has been developed, which is superior to HOMA-IR in evaluating IR [ 24 , 25 ]. Mounting evidence reveals that TyG-based indexes are associated with diseases related to chronic inflammation or metabolic disorders, including arterial stiffness [ 26 ], albuminuria [ 27 ], nonalcoholic fatty liver disease [ 28 , 29 ], hearing impairment [ 30 ], and testosterone deficiency [ 31 ]. A recent finding reported that the TyG index had a linkage to CVD in patients with ischemic heart failure after percutaneous coronary intervention [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“… 14 Currently, the TyG index has been extensively explored in diverse medical issues, such as cardiovascular disease, 6 , 7 , 8 , 9 arterial stiffness progression, 10 diabetic nephropathy, 11 new‐onset hypertension, 15 cardiometabolic diseases, 16 DM, 17 , 18 , 19 intensity care unit mortality, 20 obesity, 21 and hearing impairment. 22 However, there are relative few reports about TyG index and hypertensive nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Given the intricate nature of insulin resistance and the significant time and resource commitments it entails, simpler surrogate markers are frequently utilized for assessment. The TyG index has emerged as a dependable surrogate marker of insulin resistance (1,(10)(11)(12). Its utility has been validated across various medical conditions, including cardiovascular disease (13), hearing impairment (11), and proteinuria (10).…”
Section: Introductionmentioning
confidence: 99%
“…The TyG index has emerged as a dependable surrogate marker of insulin resistance (1,(10)(11)(12). Its utility has been validated across various medical conditions, including cardiovascular disease (13), hearing impairment (11), and proteinuria (10). Nonetheless, its relationship with gallstone prevalence remains unexplored.…”
Section: Introductionmentioning
confidence: 99%